Symposium Proceedings on Communications Architectures and Protocols 1988
DOI: 10.1145/52324.52347
|View full text |Cite
|
Sign up to set email alerts
|

Measured capacity of an Ethernet: myths and reality

Abstract: Ethernet, a 10 Mbit/set CSMA/CD network, is one of the most successful LAN technologies. Considerable confusion exists as to the actual capacity of an Ethernet, especially since some theoretical studies have examined operating regimes that are not characteristic of actual networks. Based on measurements of an actual implementation, we show that for a wide class of applications, Ethernet is capable of carrying its nominal bandwidth of useful traffic, and allocates the bandwidth fairly.We discuss how implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Secondly, the Ethernet protocol is not \fair" [7]. We conducted the following experiment t o v erify this.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the Ethernet protocol is not \fair" [7]. We conducted the following experiment t o v erify this.…”
Section: Introductionmentioning
confidence: 99%
“…For example, utilization of wired local area networks is relatively high (97%) [28] while the utilization of wireless IEEE 802.11 networks is on low level [29].…”
Section: Bandwidth Measurementmentioning
confidence: 99%
“…These assumptions sometimes lead to contradictory results. For example, research has shown maximum achievable CSMA/CD utilization of 60% with one set of assumptions [30], while later work showed utilization up to 97% with large packet sizes [4].…”
Section: Introductionmentioning
confidence: 99%